Neoadjuvant immunotherapy plus chemotherapy for squamous cell carcinoma of the paranasal sinus: a case report - Ying Sun; Guanghui Yang; Ruijie Sun; Fangli Cao (Frontiers in Oncology)
BackgroundImmune checkpoint inhibitors (ICIs) such as pembrolizumab and nivolumab are recommended as first-line therapies for recurrent and metastatic head and neck squamous cell carcinoma (HNSCC). However, their efficacy in neoadjuvant therapy remains uncertain.Case presentationWe report the case of a 68-year-old male diagnosed with HNSCC who received neoadjuvant nivolumab (anti-PD-1 inhibitor) plus nab-paclitaxel and carboplatin. Biomarkerswere assessed by immunohistochemistry, and apoptosis-related molecules were analyzed via Western blotting. The patient achieved significant tumor regression and major pathological response (MPR) without severe adverse events. Post-treatment analyses revealed PD-L1 expression increased from 30% to 50% in tumor cells, CD8+ lymphocyte infiltration significantly improved, and Ki-67 expression was markedly reduced.ConclusionsThis case highlights the potential of combining ICIs with chemotherapy in neoadjuvant settings for HNSCC, providing mechanistic insights and clinical evidence for this emerging approach. Further studies are needed to establish the optimal neoadjuvant treatment regimen and identify patient populations most likely to benefit.